Electrical conductivity, thermoelectric power, and optical properties of organo-soluble polyaniline organic semiconductor - Yakuphanoğlu, Fahrettin; Senkal, Bahire Filiz; Sarac, Ayfer (Springer, 2008)
The electrical conductivity, thermoelectric power (TEP), and optical properties of organo-soluble polyaniline doped with HCl have been investigated. The electrical conductivity and TEP of the sample increase with increasing temperature. The electrical conductivity and TEP results of the polymer suggest that it is a p-type semiconductor. The fundamental absorption edge in the polymer is formed by the direct allowed transitions, and the optical band gap value was found to be 2.79 eV. The absorption spectra for an acidic solution of the polymer indicate two new absorption bands, which are due to polaron formation. The polaron bands are responsible for the conductivity of the polymer. The TEP results indicate that the conductivity mechanism of the polymer is controlled by the large polaron hopping model.
Keywords: organic semiconductor; polyaniline; thermoelectric power